Case Study on Creating Flowcharts for Mobile Robot Line Follower Using Robomind Simulator and Non Simulator Fischertechnik - Sabril, Aulia; Suhaeb, Sutarsi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
Robot programming generally begins with creating a flowchart to define the robot's technical functions before implementing it using programming languages such as C, Ruby, or others. However, this approach has weaknesses as it requires significant time, cost, and effort, making it less efficient and effective. One solution to overcome this issue is by directly using flowcharts in the programming process. Educational toys based on Brick, such as Fischertechnik, have adopted this concept, allowing programs to be more readable, systematic, easily modified, and facilitating error identification. This study aims to compare manually created flowcharts in the Robomind simulator with those implemented using non-simulator Fischertechnik devices for the same function, namely as a mobile robot line follower. The study results indicate differences in the form and implementation of flowcharts between these two approaches. For future research, it is proposed to further compare flowcharts created in the Robomind simulator and directly uploaded to non-simulator Fischertechnik devices for the same tasks.